Daily stressors and mental health following disaster: A school‐based assessment of adolescent disaster survivors in China and Nepal. Issue 6 (6th September 2022) - Newnham, Elizabeth A.; Gao, Xue; Guragain, Bhushan; Jiao, Feng; Nathan, Elizabeth; Boyes, Mark; Leaning, Jennifer
Abstract: Postdisaster daily stressors, the economic and social challenges caused or exacerbated by disasters, have significant consequences for mental health but are rarely investigated in child and adolescent populations. We assessed posttraumatic stress symptoms (PTSS), depression, and anxiety among adolescents affected by disasters in China and Nepal and examined the specific contributions of disaster‐related trauma exposure and daily stressors across mental health outcomes. A school‐based, cross‐sectional study was conducted with a stratified random sampling design. Adolescents living in disaster‐affected areas of southern China and Nepal ( N = 4, 215, 52.7% female, age range: 15–19 years) completed translated, validated measures. Mixed effects logistic regression analyses were conducted using a priori risk factors. PTSS were reported by 22.7% of participants and were higher among Nepali adolescents but did not differ between genders. Depressive symptoms were reported by 45.2% of the sample and were higher among Nepali adolescents and girls in both countries. Across all settings, disaster‐related trauma exposure was a significant risk factor for PTSS, depressive, and anxiety symptoms, China: odds ratios ( OR s) = 1.44–2.06, Nepal, OR s = 1.21–2.53. High levels of household and interpersonal daily stressors further improved the models and contributed significantly to all mental health difficulties, China: OR s = 1.77–1.98, Nepal: OR s = 1.49–1.90. Postdisaster economic insecurity and interpersonal stressors are thus, likely to worsen adolescent mental health outcomes. Programs that identify and address structural inequalities for adolescents in disaster‐affected settings will have cascading effects for mental health.